Multiparty micropayments for ad hoc networks - O'MAHONY, DONAL; TEWARI, HITESH (My University, 2003)
The majority of ad hoc networks and their associated applications have been designed with closed user groups in mind. In such scenarios all the nodes in the network usually belong to a single authority and are configured to cooperate in the relaying of packets within the network. In recent years however, ad hoc networks have also found their way into everyday networking environments, where mobile devices may be under the administrative control of individual users. These users may not necessarily be motivated to provide services for free to others in the network. A typical situation could be where a node may wish to relay packets through a number of intermediate nodes in the ad hoc network, to access services in the fixed network. In this paper we present a lightweight payment scheme based on hash chains, which allows a node to pay others who relay packets on its behalf in real-time. Also due to the dynamic nature of an ad hoc network, the topology of the network can change unpredictably. The design of the payment scheme is flexible enough to be able to cope with such route changes, without the need to contact a trusted third party such as a bank or broker to pay the nodes in the new path.
Proceedings of the IEEE Wireless Communications and Networking Conference (WCNC) 2003
PUBLISHED
New Orleans, Louisiana
Keywords: ad hoc networks; distributed transient network; IBSS